DEKLOROFILASI EKSTRAK PROTEASE DARI TANAMAN BIDURI (Calotropis gigantea) DENGAN ABSORBAN CELITE - Yuli Witono (The East Java Biological Society, 2008)
Biduri’ plant is a wild bush in tropical countries which is one of potential protease source. However, protease extracted from leaf and stamp top of biduri is still green in color due to contain a protein bounding-chlorophyll. It would be problem if it is used for some food. The objective of this rearch was to study a dechloroplyllation technique in order to obtain protease with low chlorophyll content but high specific activity. The results showed that the best dechlorophyllation method of biduri protease could be eluted by celite absorbance. The first step elution was obtained 16 ml filtrate of biduri protease with low chlorophyll. Consist to the result above also decreased protein content, with loading capacity was 1.067 gram biduri/gram celite or 0.015 μg chlorophyll/gram celite. However in the second step elution, after biduri filtrate has been freezed for 12 hours was obtained the dechlorophylated biduri protease was higher in loading volume. Resulting in increased of loading capacity to be 2.13 gram biduri/gram celite or 0.004 μg chlorophyll/gram celite. The chlorophyll decreased to about < 44% of chlorophyll from the first step elution, even the specific activity increased 286% compared with the first step elution.